GEOGRAPHIC INFORMATION SYSTEM (GIS) USES A* ALGORITHM FOR SORTING NEAREST UMKM LOCATIONS - Nurhamni, Nurhamni (Universitas Lampung, 2025)
Abstract. UMKM are businesses that have the characteristics of a region with various types of categories. The number of categories provides obstacles for the community in choosing the UMKM they want to visit. Mapping and sorting UMKM location in Bireuen Regency needs to be done to make it easier for people to choose UMKM and display routes to the location of these UMKM. The author built a Geographic Information System (GIS) using the A* algorithm which aims to sort the closest UMKM according to category and display the closest route to the location. The data used consists of 320 with a division of 7 culinary categories, 2 clothing categories and 2 handicraft (craf). The A* algorithm is the calculation of the lowest estimated cost f(n) by summing the path distance between 2 road intersection points and the heuristic value h(n) of the current node as a basis for finding the shortest route and providing the user with information on which nodes around the user can be passed by comparing the smallest f(n) distance. The results of research on 10 sample data show that the A* algorithm is able to sort the closest route with a MAPE accuracy rate of 1.1%.